An overview of stereotactic body radiation therapy for hepatocellular carcinoma. (2nd April 2020) - Kimura, Tomoki; Doi, Yoshiko; Takahashi, Sigeo; Kubo, Katsumaro; Imano, Nobuki; Takeuchi, Yuki; Takahashi, Ippei; Nishibuchi, Ikuno; Murakami, Yuji; Kenjo, Masahiro; Nagata, Yasushi
ABSTRACT: Introduction : According to several guidelines, stereotactic body radiation therapy (SBRT) for early hepatocellular carcinoma (HCC) can be considered an alternative to other modalities, such as resection, radiofrequency ablation (RFA), and transarterial chemoembolization (TACE), or when these therapies have failed or are contraindicated. This article reviews the current status of SBRT for the treatment of HCC. Areas covered : From the results of many retrospective reports, SBRT is a promising modality with an excellent local control of almost 90% at 2–3 years and acceptable toxicities. Currently there are no randomized trials to compare SBRT and other modalities, such as resection, RFA, and TACE, but many retrospective reports and propensity score matching have shown that SBRT is comparable to the different modalities. Repeated SBRT for intra-hepatic recurrent HCC also resulted in high local control with safety and satisfactory overall survival, which were comparable to those of other curative local treatments. Expert opinion : Despite the good results of SBRT, the conclusions of the comparisons of SBRT and other modalities are still controversial. Further studies, including randomized phase III studies to define that patients are more suitable for each curative local treatment, are needed.